(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2019)
The main aim of the work was to assess the state and changes in the level of infrastructure in rural and urban-rural communes of the West Pomeranian Voivodeship in 2004–2017. The study was conducted using a synthetic analysis of the most important elements of social and technical infrastructure. The analytical part examined the level and spatial diversity of social and technical infrastructure in rural and urban-rural communes of the region in 2017 and the changes that took place in this respect compared to 2004. In accordance with the adopted research hypothesis, the conducted analysis showed that the level of rural and urban-rural communes infrastructure in the West Pomeranian Voivodeship is directly related to their location. The areas in the coastal zone and in the zone of impact of large cities are characterized by a much higher level. The lower level of the studied phenomenon was observed in the agro-forest areas located in the southern and eastern part of the region.